Common pediatric medical procedures. Simple removal of a foreign body - Kelleher, Kelly J.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2014)
A complete review and demonstration of the procedure for simple removal of foreign body, including demonstrations of removal of splinters, fishhooks, and foreign bodies from the ear and nose.
Presenter: Kelly J. Kelleher.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 16, 2020)
Keywords: Ear -- Foreign bodies; Nose -- Foreign bodies; Children -- Wounds and injuries -- Nursing; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films